Previous consultation to rethink the constitutional theory in Peru - Gonzales Mantilla, Gorki (2014)
It’s not possible to forget the indigenous and native communities as a key element in the Peruvian  constitutional  structure.  Previous consultation is a reflection of this. However,this has not always been so. For a long time,the economic and cultural hegemonies that influenced the constitutional conceptions putaside the fundamental diversity and dialogue.In this article, the author alludes to Low- intensity Constitutionalism which marked distance between political events and social conflict. For the author, the emergence of prior consultation is a sign of historical grievance and that in this context, a constitutional theory that does not put aside cultural diversity is necessary, since political representation is legitimized when the State ensures the rightsof all citizens.